Feeling the Force: Measurements of Platelet Contraction and Their Diagnostic Implications - Williams, Evelyn Kendall; Oshinowo, Oluwamayokun; Ravindran, Abhijit; Lam, Wilbur A.; Myers, David R. (Seminars in Thrombosis and Hemostasis, 2019)
In addition to the classical biological and biochemical framework, blood clots can also be considered as active biomaterials composed of dynamically contracting platelets, nascent polymeric fibrin that functions as a matrix scaffold, and entrapped blood cells. As platelets sense, rearrange, and apply forces to the surrounding microenvironment, they dramatically change the material properties of the nascent clot, increasing its stiffness by an order of magnitude. Hence, the mechanical properties of blood clots are intricately tied to the forces applied by individual platelets. Research has also shown that the pathophysiological changes in clot mechanical properties are associated with bleeding and clotting disorders, cancer, stroke, ischemic heart disease, and more. By approaching the study of hemostasis and thrombosis from a biophysical and mechanical perspective, important insights have been made into how the mechanics of clotting and the forces applied by platelets are linked to various diseases. This review will familiarize the reader with a mechanics framework that is contextualized with relevant biology. The review also includes a discussion of relevant tools used to study platelet forces either directly or indirectly, and finally, concludes with a summary of potential links between clotting forces and disease.
Keywords: blood clot; platelet; clot contraction; bleeding disorders; thrombotic disease